Effect of cation–anion balance in feed on urine pH in rabbits in comparison with other species. Issue 6 (16th March 2017) - Heer, F.; Dobenecker, B.; Kienzle, E.
Summary: In the present investigation, the impact of diet composition on urine pH in rabbits was compared with previous studies on rabbits, cats, dogs, pigs and horses. A total of 13 dwarf rabbits were fed six different diets with a cation–anion balance (CAB) between −39 and +320 mmol/kg dry matter (DM) using ammonium chloride (NH4 Cl) as an acidifier. CAB was calculated as follows: CAB (mmol/kg DM) = 49.9*Ca + 82.3*Mg +43.5*Na + 25.6*K − 59*P − 62.4*S − 28.2*Cl; minerals in g/kg DM. Urine, faeces and blood were collected. Urine pH ranged from 5.26 ± 0.22 at a CAB of −39 mmol/kg DM to 8.56 ± 0.24 at a CAB of +320 mmol/kg DM. A low CAB in the feed reduced blood pH and blood base excess significantly. Renal excretion of Ca, P, Na and Mg and water was significantly higher in rabbits eating acidifying diets. In comparison with other species, rabbits reacted to acidifying diets in a similar way as cats, dogs and pigs. Rabbits on a mildly alkalizing diet, however, had a trend to higher urine pH than other monogastric species on such diets (cats, dogs, pigs, horses).